(untitled) (Journal of Medical Sciences, 2022)
Despite the improvements of resin composites restorative materials and techniques, postoperative hypersensitivity following placement of composite restoration yet remains a problem for both the dentist and the patient. Aim: To evaluate the effectiveness of a Novaseal cavity liner in preventing the occurrence of postoperative hypersensitivity (POH) in class I and II posterior composite restorations. Materials and Methods: A total of 296 posterior composite restorations were placed in 148 patients of both genders (mean age 27.7 ±8.02 Yrs). Each patient has homologous contralateral occlusal or proximal-occlusal caries lesions in premolars and molars teeth. All teeth were restored with a total-etch adhesive system; Tetric® N-Bond and Tetric® N-Ceram resin composite (Ivoclar Vivadent). For each patient, one tooth was chosen at random to be restored with a layer of Novaseal cavity liner, and the contralateral tooth was restored without a liner. POH to various stimuli was evaluated at weeks 1, 4, & 13 post-treatment using the Visual Analog Scale (VAS). Data were statistically analyzed by Chi-Square and Fischer Exact tests. Results: No statistically significant difference in the occurrence of POH was observed between the restorations performed with or without Novaseal cavity liner (P>0.05). Out of 296 restorations placed with the two restorative techniques; only five restorations; 5/296 (1.7%) reported POH to cold at week 1. Among those; three restorations; 3/148 (2%) placed with cavity liner, reported mild and moderate POH (VAS=2, 3 & 5), and two restorations; 2/148 (1.4%) placed without a liner reported mild POH (VAS=3). No POH was reported at weeks 4 and 13 for the two restorative techniques. Conclusions: Novaseal cavity liner could not totally prevent POH in class I and II posterior composite restorations. POH can occur irrespective of the use of a cavity liner.